A second monoclinic polymorph of N-(diethylaminothiocarbonyl)-N′-phenylbenzamidine - Schröder, Bernd (International Union of Crystallography, 2011)
The asymmetric unit of the title compound, C(18)H(21)N(3)S, contains five molecules. The equivalent bond distances in the five molecules are in excellent agreement, the r.m.s. fit being within 0.007 Å. The five molecules are linked into a chain consisting of alternating pseudo-enantiomers by N—H⋯S hydrogen bonds supplemented by weak C—H⋯π interactions. The action of a glide plane links the asymmetric unit into an extended chain. A polymorph of the title compound with one molecule in the asymmetric unit was reported by Braun et al. [Cryst. Res. Technol. (1988), 23, 35–39].